(untitled) (Journal of Geography and Environmental Management, 2017)
In this paper, we estimate the stability of buildings and structures for seismic fluctuations in the Almaty city, because frequent earthquakes threaten to life and health of population. In conditions of constant expansion and construction, we always must always worth considering the seismic resistance of buildings, because threaten to life of population during earthquakes is the basis for the beginning of erection of structures. To remain unharmed among in the seismic zone. The aim is to study the condition of buildings in Almaty on characteristics of seismic safety. Objectives of the study: - study of common types of buildings in Almaty; - carrying out calculations of the stability of buildings; We used the method of analysis of the common types of buildings and structures of the city, measuring their resistance to seismic vibrations. This article shows the calculation of the stability levels of buildings in different parts of the city to seismic fluctuations. Data are given on the levels of design seismic resistance of most of the structures, possible indicators of their stability are calculated. As the results showed, the stability of buildings and structures of the city directly depends on their location on the city map, which is due to the reduction of seismic activity in the direction from the lower part to the upper one. According to the conclusion, it is necessary to increase the number of design organizations responsible for the quality of construction, as well as to use a different structure and approach to the erection of buildings in different parts of the city.